(untitled) (Bangladesh Journal of Agricultural Research, 2013)
A field experiment was conducted at the Regional Agricultural Research Station, Ishurdi, Pabna, Bangladesh during 2008-09 and 2009-2010 to find out the suitable intercrop combination of sesame with mukhikachu for getting higher productivity and economic return. Five treatments comprised of T1 = sole mukhikachu (double row:20 cm/55 cm/20 cm × 45 cm), T2=sole sesame (30 cm×5 cm), T3 = mukhikachu (double row:20 cm/55 cm/20 cm × 45 cm) + one row sesame (30%), T4 = mukhikachu (double row:20 cm/55 cm/20 cm × 45 cm) + two row sesame (60%), and T5 = mukhikachu (double row:20 cm/55 cm/20 cm × 45 cm) + sesame broadcast (100%). The results showed that intercropping systems affected the cormel yield of mukhikachu and seed yield of sesame. Mukhikachu yield decreased with the increase of sesame population in intercropped combination. The highest mean mukhikachu equivalent yield (15.65 t/ha), land equivalent ratio (1.83), gross return (Tk.187585/ha), gross margin (Tk. 114265/ha), and benefit cost ratio (2.56) were obtained from two rows of sesame (30 cm × 5 cm) in between two double rows (20 cm/55 cm/20 cm × 45 cm) of mukhikachu. Sole crop of sesame gave the lowest mukhikachu equivalent yield (4.02 t/ha), gross return (Tk.48125/ha), gross margin (Tk. 19655/ha), and benefit cost ratio (1.69). Two years’ study revealed that two rows of sesame (60%) in between two double rows (20 cm/55 cm/20 cm × 45 cm) of mukhikachu was found profitable intercropping combination. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14387 Bangladesh J. Agril. Res. 37(4): 625-634, December 2012